Synthesis of Bio-hexane and Bio-Hexene from Sorbitol Using Formic Acid as Reducing Agent - Michael Gunawan; Tedi Hudaya; Tatang Hernas Soerawidjaja (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Sorbitol (C6H14O6) is a sugar alcohol that can be synthesized from cellulose and has a similar skeletal structure as hexane (C6H14) so that it can straightforwardly be converted to hexane through deoxygenation. The bio-hydrocarbon synthesis from sorbitol in this investigation consisted of two main processes, namely synthesis of 2-iodohexane and deiodization of 2-iodohexane. The synthesis of 2-iodohexane from sorbitol and hydroiodic acid (HI) was conducted in a reflux system, to which formic acid as reducing agent was added gradually during the reaction to regenerate the iodine back to HI. The HI/sorbitol ratio (2:1 and 5:1), reaction temperature (90 °C, 105 °C, and 120 °C), and reaction time (between 2 and 6 hours) were varied throughout the experiment. Deiodization of 2-iodohexane was conducted via gas phase pyrolysis at various temperatures (265 °C to 285 °C) and reaction times (30 and 45 minutes). The sorbitol was effectively converted to a mixture of 2-iodohexane, hexane and other bio-hydrocarbons, with a 2-iodohexane yield of 23.15%. In the optimal reaction condition, pyrolysis of 2-iodohexane resulted in bio-hydrocarbon with a yield of 77.52%. The resulted hydrocarbon products were mixtures consisting of alkanes and alkenes.